THE ROLE OF WRITERS IN THE FORMATION AND DEVELOPMENT OF UKRAINIAN CHILDREN'S PERIODICALS IN TRANSCARPATIA IN THE 1920s-1930s XX CENTURY - Lemak, Oksana (Mountain School of Ukrainian Carpaty, 2022)
The raised problem is actualized by the scientific interest and practical significance of the study of the historical experience of the development of children's periodicals in Ukraine. Its interesting original page is the process of creation and development of children's magazines in Transcarpathia in the 20s and 30s. ХХ th century The purpose and task of the research is to find out the role and contribution of Ukrainian literati (poets, writers, editors) in the formation and development of children's periodicals of Transcarpathia in the 20s and 30s of the ХХth century. The following methods were used in the preparation of the study: heuristic-search; analysis and synthesis; content analysis and discourse analysis; biographical. The results of the research consist in clarifying the role and contribution of Ukrainian writers and teachers (Agustyn Voloshyn, Oleksandr Markush, Ivan Pankevich, Pavlo Kukuruza, etc.) in the founding and development of the children's magazines "Wreath for Podkarpatskyi Children" and "Pchilka". Their role in publishing the youth magazine "Nash nadny kray" is shown. Emphasis is placed on highlighting the organizational and methodological experience of the Pchilka magazine editorial office in organizing school holidays in honor of Ukrainian writers, school libraries and reading rooms, exhibitions, reading circles (clubs). The forms and methods of establishing feedback from the "Bee" editorial office with readers are shown, which is manifested in the introduction of special sections, the publication of their poems and stories on the magazine's page, etc. The conclusions state that famous Ukrainian writers and poets of Transcarpathia and emigrants from Galicia and Trans- Dnipro Ukraine were prominent initiators and organizers of the process of founding and developing children's periodicals in Transcarpathia in the 20s and 30s of the XX century. As professional writers and editors and, in the vast majority, professional teachers, they ensured that children's magazines not only presented the best achievements of children's poetry and prose to the reader, but also became important effective organizational and methodical centers for the formation and development of interest in the artistic word, aesthetic tastes, reading culture. The experience of the editors of children's magazines in stimulating the creative activity of schoolchildren, establishing feedback with the reader, developing methods for arranging school libraries, exhibitions, organizing group work, etc., has not lost its relevance.